2013
DOI: 10.1371/journal.pone.0072708
|View full text |Cite
|
Sign up to set email alerts
|

New Blocking Antibodies Impede Adhesion, Migration and Survival of Ovarian Cancer Cells, Highlighting MFGE8 as a Potential Therapeutic Target of Human Ovarian Carcinoma

Abstract: Milk Fat Globule – EGF – factor VIII (MFGE8), also called lactadherin, is a secreted protein, which binds extracellularly to phosphatidylserine and to αvβ3 and αvβ5 integrins. On human and mouse cells expressing these integrins, such as endothelial cells, phagocytes and some tumors, MFGE8/lactadherin has been shown to promote survival, epithelial to mesenchymal transition and phagocytosis. A protumoral function of MFGE8 has consequently been documented for a few types of human cancers, including melanoma, a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 19 publications
5
37
1
Order By: Relevance
“…We examined MFG‐E8 expression in human esophageal squamous cell carcinoma using IHC staining and found that some of the cells abundantly express MFG‐E8, as shown in other types of cancer . As the IHC staining of the samples showed that the expression of MFG‐E8 was more abundant in cancer cells than in macrophages or other stromal cells, MFG‐E8 from cancer cells appears to play an important role in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We examined MFG‐E8 expression in human esophageal squamous cell carcinoma using IHC staining and found that some of the cells abundantly express MFG‐E8, as shown in other types of cancer . As the IHC staining of the samples showed that the expression of MFG‐E8 was more abundant in cancer cells than in macrophages or other stromal cells, MFG‐E8 from cancer cells appears to play an important role in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 87%
“…Milk fat globule‐epidermal growth factor factor 8 is reported to be expressed in several types of human cancer cells, as well as immune‐related cells. Such expression has been found to be associated with tumor proliferation, epithelial‐mesenchymal transition, cell migration, M2 macrophage polarization, and the induction of Tregs . However, there are limited reports that clarified its prognostic impact on cancer patients .…”
Section: Introductionmentioning
confidence: 99%
“…We showed that KMT2D silencing leads to inactivation of a subset of KMT2D-bound enhancers (reduced H3K4me1 and H3K27Ac) and downregulation of a subset of genes that are critical for cell migration, including MFGE8 and RPL39L . Downregulation of either gene in several cancer types, and in melanoma and breast carcinomas specifically, reduces cell migration, and their expression correlates with a more aggressive phenotype and unfavorable outcome in the patients (37)(38)(39). Notably, KMT2D target genes were the most proximal to the KMT2D-dependent enhancers, suggesting that KMT2D promotes tumorigenesis by deregulating enhancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…CD14 + cells were enriched by magnetic sorting (Miltenyi Biotec) and cultured at 1-2 million cells per mL for 5 d in RPMI 1640 (Gibco) supplemented with 10% FCS (Biowest), 50 μM 2-ME, 10 mM Hepes, 100 IU/mL penicillin and 100 μg/mL streptomycin (Gibco) in the presence of IL-4 and GM-CSF (50 ng/mL and 100 ng/mL, respectively; Miltenyi Biotec). Cell lines HEK293T, RPE-1 (37), HeLa-CIITA (32), MDA-MB-231, SHIN, IGROV-1 (38), and OV2008 were cultured in DMEMglutamax (or RPMI-glutamax for IGROV-1) supplemented with 10% FCS (Lonza), 100 IU/mL penicillin, and 100 μg/mL streptomycin (Gibco).…”
Section: Methodsmentioning
confidence: 99%